Experimental study of nanofluid flow and heat transfer over microscale backward- and forward-facing steps - Kherbeet A.S.; Mohammed H.A.; Salman B.H.; Ahmed H.E.; Alawi O.A.; Rashidi M.M. (Elsevier Inc., 2023)
Facings; Forced convection; Heat transfer; Nusselt number; Reynolds number; Rivers; Backward facing step; Distilled water; Experimental; Friction factors; Heat transfer characteristics; Microscale forward-facing step; Nanofluid flow; Nanofluids; Nanofluidics